A PRELIMINARY STUDY OF HEALTH PROBLEMS AMONG CONSTRUCTION WORKERS IN MALAYSIA - Zainon, Nurshuhada; Chuing, Loo Siaw; Mohd-Rahim, F.A.; Aziz, Nur Mardhiyah; Che Wan Ahmad Pauzi, Che Wan Nor Shahirah (Journal of Surveying, Construction and Property, 2018)
The Department of Occupational, Safety and Health reported that out of 172 investigated construction accidents in 2014, 42% involved death. Although this rate is lower than that for manufacturing plants, lost work-day rates are higher for several individual construction trades and for certain types of injuries. Since the lost work-day rates for small to medium sized construction companies are higher than that of similar-sized manufacturing plants, it will cause economic loss to the construction companies more than the others. Studies have found that health conditions also contribute to construction safety issues. These raise questions about the health level among construction workers in Malaysia prior to looking at their effects onto construction safety issues. Therefore, this preliminary study aims to identify health issues among them. A total of 335 respondents responded to a survey distributed among construction workers. It was found that the top health problems recorded to affect the workers were musculoskeletal disorder, eyes, nose and throat problem, fatigue and headache. The findings provided a further insight on the seriousness of certain types of health problems that affect construction workers working in the construction industry, hence medical cost or insurance should be an important cost element that needs to be considered by a Quantity Surveyor in building up a project cost.